Utilization Of Onion (Allium cepa) Ice Cream - Honey Skynely F. Mondano; Francis Rey D. Craecle,; Angelica Mae E. Condez; Anjaneth F. Montalban; Carmen Angela N. Nacis; Sheianerose N. Niog; Abby Maxwell G. Saurin; Rena E. Servidad (IC-ITECHS, 2022)
This experimental study was conducted to determine the level of perception of the evaluators on Onion (Allium cepa) Ice Cream as to appearance, aroma, taste, texture and general acceptability in two formulations. This study alsodetermined the significant difference in the level of perception of the evaluators on the two formulations of Onion Ice Cream in all its sensory characteristics and general acceptability. The study made use of the Five-Point Likert Scale to determine the perception of the evaluators on the finished product as to appearance, aroma, taste and texture and the Nine-Point Hedonic Scale for the general acceptability. Mean, Standard Deviation and t-test at 0.05 level of significance were used as statistical tools. Sensory Evaluation Checklist based on Five-Point Likert Scale and Nine-Point Hedonic Scale was administered to collect data. The evaluators of the study were the thirty (30) resident vendors of Barangay La Consolacion, Miagao, Iloilo that were selected through purposive sampling. The study was conducted during the second semester of the School Year 2021-2022. The results of the study revealed that as to appearance, Formulation A (250 grams white onion) was perceived as white and Formulation B (500 grams white onion) was perceived to have a slightly white appearance. For the aroma, both formulations was perceived as moderately strong onion aroma. In terms of taste, Formulation A was perceived as moderately onion taste while Formulation B was perceived as very onion taste. The texture of Formulation A was perceived as extremely smooth while the Formulation B was perceived as smooth. As to general acceptability, Formulations A and B was both perceived as like very much by the evaluators. Inferential statistics also revealed that there was a significant difference in the perception of evaluators as appearance, taste and texture in white onion (Allium Cepa) in making ice cream. However, there was no significant difference in the perception of evaluators as to aroma. The findings further revealed that there was no significant difference in the perception of the evaluators as to general acceptability of the two formulations of Onion (Allium cepa) Ice Cream. This implied that the Onion Ice Cream prepared by the researchers was accepted by the evaluators in all its sensory characteristics in two formulations and so for the general acceptability. The researchers came to the conclusion that white onion is a potential main ingredient in making ice cream. Therefore, farmers and white onion growers should be encouraged to plant more white onion for mass production of the product to be sold at barangay La Consolacion and other barangays for their additional income. Further studies or even a follow-up on development of other recipes using onion is also encouraged to ascertain the validity of the result and to determine the proximate analysis and shelf life of the onion ice cream.